(untitled) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2021)
This article analyzes the social representations of teachers about the Recent Present History (RPH) of Chile and its teaching in sixth basic year. It is an educational research that is inserted in the Field of Didactics of Social Sciences. The data were obtained from 11 questionnaires and 11 in-depth interviews with History, Geography and Social Sciences teachers from educational establishments in the Metropolitan Region and the Valparaíso Region in Chile. The objective was to identify the origin of their representations. Which allow us to approach to know the various variants that influence the construction of the thought of the teachers about this historical period. The construction of imaginaries is an antecedent that also influences the moment of carrying out the teaching of the contents. This research analyzes the following aspects: a) the origins of social representations about RPH in Chile; b) the influence of teacher’s thinking on RPH teaching; c) the periodization of RPH; d) the contents that teachers recognize as part of the RPH of Chile; e) the contents of the RPH of Chile that teachers teach in sixth basic year; f) the purposes of teaching the RPH in sixth basic year.